2021
DOI: 10.1177/08969205211046658
|View full text |Cite
|
Sign up to set email alerts
|

One of the Good Ones: Rhetorical Maneuvers of Whiteness

Abstract: Drawing on the literature on white habitus, colorblindness, diversity ideology, and happy talk, I argue that rhetorical maneuvers are key aspects of white habitus that allow whites to construct a non-racist self by drawing on colorblind discourses. To explore how white habitus influences interview dynamics when the respondent and interviewer are of a different race, I conducted 48 interviews with whites from rural and urban areas of the Greater Buffalo Area. Specifically, I examine the relationship between whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…My positionality was important for allowing me to gain access to participants in this community due to my partially shared ethnic background—a phenomena which has been previously reflected in qualitative research (Adu‐Ampong and Adams 2020; Berkovic et al. 2020; Rabia 2021). As a Hispanic woman who is from Southern Colorado, I was able to easily engage with the local population despite never having lived in Taos previously.…”
Section: Methods and Field Sitementioning
confidence: 89%
“…My positionality was important for allowing me to gain access to participants in this community due to my partially shared ethnic background—a phenomena which has been previously reflected in qualitative research (Adu‐Ampong and Adams 2020; Berkovic et al. 2020; Rabia 2021). As a Hispanic woman who is from Southern Colorado, I was able to easily engage with the local population despite never having lived in Taos previously.…”
Section: Methods and Field Sitementioning
confidence: 89%
“…For example, in response to the Maher Incident, the SLC board explicitly called for an investigation of "both sides" as a means to avoid confronting the racial violence that had occurred [41]. This sort of rhetoric that treats racism as a 'both sides' issue "where two sides can agree to disagree" according to Rabii, causes harm by "falsely equat[ing] racism with being victimized by it" [54] (p. 1283). In recognition of this false equivalency, Nabors retorted "I don't believe you don't know both sides", [41] suggesting that the two parties were distinct; on one side was Maher, who acted as a racist educator and on the other were the Black students who fell victim to his racist verbal attack.…”
Section: Avoidancementioning
confidence: 99%
“…For instance, in what he identifies as the "differentiation frame," Rabii (2022) examines the rhetorical maneuvers used by whites to distinguish themselves from "bad apples" and foster a non-racist self-presentation in hopes of being identified as "one of the good ones." White respondents engaged in "credentialing" by "listing criteria" as evidence of their non-racist identity, such as situations in which "they confronted discrimination, their tolerant upbringing, and their understanding of the benefits of diversity" (Rabii 2022(Rabii : 1276. Similarly, in his study of white student leaders at a predominately white university, Foste (2020: 40) found an "intense preoccupation with a presentation of the self" as racially progressive.…”
Section: Racism White Identity and Self-conceptmentioning
confidence: 99%
“…This good identity is often constructed as “different” or “better” in relation to other whites. For instance, in what he identifies as the “differentiation frame,” Rabii (2022) examines the rhetorical maneuvers used by whites to distinguish themselves from “bad apples” and foster a non‐racist self‐presentation in hopes of being identified as “one of the good ones.” White respondents engaged in “credentialing” by “listing criteria” as evidence of their non‐racist identity, such as situations in which “they confronted discrimination, their tolerant upbringing, and their understanding of the benefits of diversity” (Rabii 2022: 1276). Similarly, in his study of white student leaders at a predominately white university, Foste (2020: 40) found an “intense preoccupation with a presentation of the self” as racially progressive.…”
Section: Theoretical Frameworkmentioning
confidence: 99%